ANALYSIS OF STUDENT LEARNING CHARACTERISTICS AT LOW-CLASS ELEMENTARY SCHOOL LEVEL AT MI MUHAMMADIYAH 1 UJUNGPANGKAH - GILANG SURYANI PUTRI AL FITRI; Ismail Marzuki, S.Ag., M.Pd (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2023)
This study was conducted in the third grade of MI Muhammadiyah 1 Ujungpangkah to determine students' learning styles and how they affect the learning process. The research methods used were observation, interviews with grade 3 teachers, and a learning style questionnaire filled out by 15 students. The analysis revealed that the visual learning style was dominant at 53%, followed by kinesthetic at 13% and auditory at 33%. This highlights the importance of providing diverse learning materials that cater to students' preferred learning styles. The learning process should encourage active participation and inclusivity to explore student's potential.